Puff, the magic dragon - Yarrow, Peter, 1938-2025; Lipton, Lenny, 1940-2022; Puybaret, Éric (New York : Sterling Pub., 2007)
The adventures of a boy and his dragon friend are recounted in this classic song from the 1960s.
"Includes a four-song CD recorded by Peter Yarrow (of Peter, Paul & Mary) with Bethany & Rufus"--Cover.
Keywords: Children's songs, English -- United States -- Texts; Dragons -- Songs and music; Songs